Recensión a P.-O.H. Wikström, D. Oberwittler, K. Treiber y B. Hardie. "Breaking rules. The social and situational dynamics of young people’s urban crime". Oxford: Oxford University Press, 2012 (479 páginas) - Janosch González, Heriberto (Revista de Derecho Penal y Criminología, 2019)
-